ANALISIS NILAI COMPUTED TOMOGRAPHY DOSE INDEX (CTDI) PADA PHANTOM KEPALA DI INSTALASI RADIOLOGI RUMAH SAKIT UMUM DAERAH SAYANG RAKYAT MAKASSAR - Ilham, Ilham; Zelviani, Sri; Jumardin, Jumardin; Bariah, Khaerul (JOURNAL ONLINE OF PHYSICS, 2024)
This research aims to determine the CTDI value on a CT Scan aircraft using Dose Profiler and to determine the comparison of the CTDI (Computed Tomography Dose Index) value on the surface of each measurement position. The measurement method was carried out by measuring the CT Scan radiation dose with the CTDI value on the phantom using a RaySafe multimeter at a voltage of 130 kV, using a thickness of 10 mm, a time current accuracy of 100 mAs, 200 mAs and 300 mAs. The research results show the dose received on the surface of each type of phantom position with different time current accuracy respectively for a time current of 100 mAs at the center (9.139 mGy), type 1 (9.606 mGy), type 2 (9.170) type 3 (9.221) , and type 4 (9,210). A time current of 200 mAs is found at the center (9,110 mGy), edge 1 (9,578 mGy), edge 2 (9,546 mGy), edge 3 (9,224 mGy), and edge 4 (9,200 mGy). A time current of 300 mAs is found at the center position (18.39 mGy), edge 1 (19.33 mGy), edge 2 (19.18 mGy), edge 3 (18.48 mGy), and 4 (18.51 mGy) . Time-current variations affect the radiation dose that can be received by the phantom and have a linear influence on the CTDIvol value.